Answer:
x> 13
Step-by-step explanation:
x-4 >9
Add 4 to each side
x-4+4 >9+4
x> 13
Answer:
8x8
6
GCF
Step-by-step explanation:
We are told that f(1) = -1.5, and that f(n+1) = -2f(n).
Then: f(2) = -2f(1) = -2(-1.5) = +3 (answer)
Answer:
a = - 4
Step-by-step explanation:
Given x = - 2 is a root then f(- 2) = 0
f(x) = x³ + x² + ax - 4, thus
f(- 2) = (- 2)³ + (- 2)² - 2a - 4 = 0, that is
f(- 2) = - 8 + 4 - 2a - 4 = 0, thus
- 8 - 2a = 0 ( add 8 to both sides )
- 2a = 8 ( divide both sides by - 2 )
a = - 4
Answer:
Option (1)
Step-by-step explanation:
By using triangle sum theorem in the given triangle,
(5x - 7)° + (11x - 4)° + (3x + 1)° = 180°
(5x + 11x + 3x) - (7 + 4 - 1) = 180
19x - 10 = 180
19x = 190
x = 10
Therefore, (3x + 1)° = 30 + 1
= 30°
(11x - 4)° = 110 - 4
= 106°
(5x - 7)° = 43°
Therefore, Option (1) will be the correct option.